2014
DOI: 10.1182/blood.v124.21.2558.2558
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Body Mass Index Among Children and Adults Undergoing Allogeneic Hematopoietic Cell Transplantation: Clinical Characteristics and Outcomes

Abstract: Obesity is a serious public health problem accompanying changes in diet and physical activity. The rising prevalence of obesity may influence the outcomes of hematopoietic cell transplantation (HCT). We studied 898 children and adults receiving first-time allogeneic bone marrow or peripheral blood stem cell transplants between 2004 and 2012 at the University of Michigan. Pre-transplant body mass index (BMI) was calculated using height and weight measurements and treated as a continuous variable. Recipients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
(61 reference statements)
0
9
0
2
Order By: Relevance
“…ST2 was also included in a biomarkers panel predictive for cGvHD development, GvHD severity and TRM [24]. Finally, pretransplant ST2 levels were reported being higher in obese patients as compared to normal weight patients [25]. Our result displayed that soluble ST2 levels increased from baseline to both aGvHD and cGvHD onset, but no differences were seen in terms of response to treatment.…”
Section: Discussionmentioning
confidence: 58%
“…ST2 was also included in a biomarkers panel predictive for cGvHD development, GvHD severity and TRM [24]. Finally, pretransplant ST2 levels were reported being higher in obese patients as compared to normal weight patients [25]. Our result displayed that soluble ST2 levels increased from baseline to both aGvHD and cGvHD onset, but no differences were seen in terms of response to treatment.…”
Section: Discussionmentioning
confidence: 58%
“…Gleimer et al [2] analyzed the effect of BMI in 898 children and adults after a first allogeneic HCT. Outcomes evaluated included overall survival, NRM, relapse, and cumulative incidences of acute and chronic GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…Since that time, several single and multicenter analyses have assessed the effect of additional measures of body habitus, including body mass index (BMI), body surface area (BSA), and weight loss during transplantation, on transplantation outcomes. These studies, summarized in a recent review, had varying results and sometimes reached disparate conclusions [2]. Comparing the results of these studies is difficult because of the diversity of patient populations studied, differing duration of follow-up, small patient numbers, and diagnosis-or conditioning regimen-restricted patient groups.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, as the obesity epidemic continues, it may be assumed that the increased visceral fat composition and associated metabolic inflammation observed in obese recipients probably also contributes to increased GVHD severity in these patient populations. Epidemiological studies have reported that obese patients often experience a higher risk of both acute and chronic GVHD [6]. However, the vast majority of HSCT and cancer preclinical studies use relatively young, lean mice (sometimes equivalent to healthy, early-adolescent humans), despite the fact that cancer is predominantly a disease of the elderly and obese.…”
Section: Factors Contributing To Differences Between Mouse and Humansmentioning
confidence: 99%